Physiotherapy Management After Washout Arthroscopy Surgery Cases for Osteoarthritis Genu Sinistra Patients - dewi adzillina, laksmita; Sutejo, Mianti Nurrizky (STIKES Telogorejo Semarang, 2024)
Osteoarthritis cases are one of the degenerative diseases caused by the reduction of joint synovial fluid and the progressive loss of articular cartilage. Currently available therapies focus on symptomatic treatment and prevention of the disease from worsening. In this day became necessitates surgical washout arthroscopy, which is used to clear infection in the original joint or after arthroplasty. After surgery, rehabilitation from physiotherapy is needed to reduce pain, increase joint range of motion, increase muscle strength and restore functional ability. Method:The patient is a 53-year-old woman complaining of pain, weakness muscles and limitation joint range of motion in the left knee after arthroscopic washout surgery 1 month ago. Physiotherapy management 4 weeks of intervention in 2 sessions with ice compress, electrotheraphy with TENS and US and exercise. Result: TENS and Ultrasound currents showed a decrease in sensation felt, increased muscle strength and joint of range motion. The provision of electrical stimulation interventions using tens and ultrasound currents for 4 weeks with 2 meetings in postoperative washout arthroscopy can be concluded to reduce pain sensation, increase the scope of joint motion and increase muscle strength in the hip.